Albumin level as a predictor of shock and recurrent shock in children with dengue hemorrhagic fever. - Napoleon Tatura, Suryadi Nicolaas; Kalensang, Priscilla; Mandei, Jose Meky; Wahyuni, Sitti; Yusuf, Irawan; Daud, Dasril (Critical Care & Shock, 2017)
Background: The severity of dengue hemorrhagic fever (DHF) can be seen from bleeding and plasma leakage manifestations. Albumin level is one of the markers of plasma leakage in dengue infection. Whether albumin can be used as a predictor of shock in DHF patients or of recurrent shock in dengue shock syndrome (DSS) patients still need to be further evaluated. Objective: To determine serum albumin level as a predictor of shock in DHF and of recurrent shock in DSS. Design: A cohort prospective study. Setting: Department of Child Health, Prof. Dr. RD Kandou Hospital, Manado, Indonesia. Patients and participants: Sixty-seven DHF patients and 58 DSS patients aged 1- to 14-yearold were enrolled in our study. Sampling was done with consecutive sampling method. The inclusion criteria were patients diagnosed with DHF/DSS based on World Health Organization (WHO) criteria (2011). The exclusion criteria were patients who received corticosteroids, blood transfusion, albumin infusion and patients with severe malnutrition. The dependent variables were shock and recurrent shock. The independent variable was serum albumin level. The relation between serum albumin level and shock or recurrent shock were analyzed using logistic regression test, power 0.80, α 0.05 and was significant if p<0.05. We used receiver operating characteristic (ROC) curve to determine prognostic factors. Data was analyzed using software SPSS v 21.0. Results: There was significant correlation between albumin level and shock in DHF patients (p=0.0001, area under the curve (AUC) 0.865, cut-off 3.05, odds ratio (OR) 17.4, sensitivity 79%, specificity 81%), but there was no correlation between albumin level and recurrent shock in DSS patients. Conclusions: Serum albumin level can be used as a predictor of shock in DHF patients but it cannot be used as predictor of recurrent shock in DSS patients.